Efektivitas Model Pembelajaran Project Based Learning Berbantuan Mind Map terhadap Keterampilan Berpikir Kritis dalam Pembelajaran Ekonomi pada Siswa Kelas X di SMAS Dharma Kirti Sengkidu - Ni Ketut Sri Budayani; Made Ary Meitriana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The low critical thinking skills of students encourage the need for solutions to control the problem. The recommended solution to this problem is the use of learning model project-based learning help mind map in economics studies. The purpose of this research is to know the use of the model project-based learning help mind map and its effectiveness in improving critical thinking skills in class X students at SMAS Dharma Kirti Sengkidu. This research is classified as experimental research by design nonequivalent control grup design. The population in this research is 49 students with a sample of class X E.A totaling 24 students as a control class using the expository model and class X E.B totaling 25 students as an experimental class using a model project-based learning help mind map. The sampling technique uses saturated sampling technique. This research was measured using multiple choice test instruments and observation sheets. Research results are interpreted fromÂ independent sample t-test, normalized gain test, and analysis of the observation sheet. The results of this research are: (1) there are differences in critical thinking skills with the experimental and control classes, (2) the percentage of student activity shows that students are more active with the experimental class than the control class, (3) the percentage of normalized gain scores with the experimental class is higher than the control class. Based on these results so that the model project-based learning help mind map effective in improving students critical thinking skills.